Chemicals-free approach control interface characteristics of nanofiltration membrane: Feasibility and mechanism insight into CEM electrolysis. (1st November 2021) - Wang, Jinlong; Liang, Heng; Tang, Xiaobin; Gan, Zhendong; Li, Guibai
Highlights: CEM electrolysis improves NF permeability by 123%–211% without chemical addition. CEM electrolysis lowers the organic concentration of NF membrane permeates. The interface of NF membranes tends to be hydrophobic, smooth, and porous. Self-aggregation of foulants contributes to the NF membrane interface to be highly permeable. Abstract: The combined fouling effect prevalent in the nanofiltration (NF) process severely limits its use. In this study, cation exchange membrane (CEM) electrolysis was performed to alleviate NF membrane fouling by controlling interface characteristics. The results revealed that CEM electrolysis (hydraulic retention time with 0.24 or 0.36 h) effectively improved NF membrane permeability by 201%–211% and achieved a stability of > 8 LMH/bar. The divalent cations were removed through CEM electrolysis, with a decrease in Ca 2+ and Mg 2+ by approximately 68.8% and 30.9%, respectively, which was related to scaling potential reduction. This softening function reduced the possibility of bridging of organics with divalent cations, which contributed to the lower molecular weight of organic matter (mainly humic substances) distributed in 1.4–23 kDa. The improved organic indicators of the NF membrane permeate quality implied that the membrane interface characteristics improved. The foulant layer on the NF membrane dominated humic substances, and biopolymers exhibited hydrophobic, smooth, and porous characteristics. The self-aggregation of foulants on the NF membrane surface stimulated the interface characteristics with high water permeability. Energy consumption confirmed the feasibility of CEM electrolysis on NF application. Thus, CEM electrolysis as a chemical-free approach that can be combined with NF and can provide guidance for NF membrane fouling in urban water treatment and water reclamation. Graphical abstract: Image, graphical abstract